Pengembangan Sistem Informasi Pembayaran Biaya Pendidikan menggunakan Teknologi Payment Gateway (Studi Kasus: SD Islam Terpadu Nurul Fikri Pati) - Qonita Nur Farhana; Issa Arwani; Dwija Wisnu Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SD Islam Terpadu Nurul Fikri Pati is a formal educational institution that applies the Student Centered Learning method where learning activities are focused on developing student character. To make this a success, synergy is needed from all stakeholders, one of which is the relationship between parents/guardians of students and the school in terms of paying for education fees. The process of recording the payment of education fees is considered less efficient and effective because it is recorded manually in the recapitulation book, then transfers the data into excel to make billing and payment reports. Furthermore, there are several problems, such as double payment data and unrecorded payment data. Based on these problems, the authors conducted research on the development of a web-based education fee payment system using the waterfall method. The analysis and design phase uses UML modeling such as use case diagrams, use case scenarios, activity diagrams, sequence diagrams, class diagrams, and physical data models. The system was developed using the Laravel framework by utilizing the integration of the payment gateway midtrans which handles payments from users. Functional testing of the system using blackbox testing which gets a percentage of 100% valid. The non-functional testing of the system was carried out using the System Usability Scale (SUS) which obtained a calculation score of 76.67, so the system was categorized as excellent, and entered into grade C which was categorized as acceptable.